2021
DOI: 10.1186/s43166-021-00065-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37 as an anti-inflammatory cytokine: does its relation to disease activity suggest its potential role in rheumatoid arthritis therapy?

Abstract: Background This study aimed to measure the serum and synovial interleukin (IL)-37 levels in rheumatoid arthritis (RA) patients compared to patients with primary knee osteoarthritis (PKOA) and healthy controls and to detect its relation to RA disease activity. Results This cross-sectional study included 50 RA patients with a mean age of 40.24 ± 8.62 years, 50 patients with PKOA with a mean age of 56.69 ± 4.21, and 40 healthy controls with a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This ranged from as low as (28.83 ng/l in RA and 11.84 in the controls) in one study 44 to as high as (712.40 ng/l in RA and 133.50 in the controls) in another study, 37 2) Some elements of the DAS 28 scoring system such as the number of tender and swelling joints and the overall health condition of the patients are largely subjected to personal judgement of the physicians which might affect the calculation of DAS28 score, 3) Differences in cohorts is another possibility, so a larger cohort might explore more positive correlation, 4) Most of the studies that reveled a positive correlation between IL-37 and DAS28 were carried on Asian populations (China) and only one study was reported among Arab population (Egypt). 45 Therefore, ethnicity is an important suggested factor to be considered when interpreting IL-37 results, 5) The concentration of IL-37 was observed to be significantly higher in the aspirated synovial fluid of RA patients than the circulation 45 and therefore synovial IL-37 might be a better marker to be considered when correlated with DAS 28 score, 6) Finally, in the current study we did not take into consideration the effect of the drugs on the IL-37 level which might be considered one of the limitations of this study. Therefore, further studies are suggested with larger cohorts to precisely compare the correlation between activity score and IL-37 taken into consideration the effects of anti-rheumatic drugs in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…This ranged from as low as (28.83 ng/l in RA and 11.84 in the controls) in one study 44 to as high as (712.40 ng/l in RA and 133.50 in the controls) in another study, 37 2) Some elements of the DAS 28 scoring system such as the number of tender and swelling joints and the overall health condition of the patients are largely subjected to personal judgement of the physicians which might affect the calculation of DAS28 score, 3) Differences in cohorts is another possibility, so a larger cohort might explore more positive correlation, 4) Most of the studies that reveled a positive correlation between IL-37 and DAS28 were carried on Asian populations (China) and only one study was reported among Arab population (Egypt). 45 Therefore, ethnicity is an important suggested factor to be considered when interpreting IL-37 results, 5) The concentration of IL-37 was observed to be significantly higher in the aspirated synovial fluid of RA patients than the circulation 45 and therefore synovial IL-37 might be a better marker to be considered when correlated with DAS 28 score, 6) Finally, in the current study we did not take into consideration the effect of the drugs on the IL-37 level which might be considered one of the limitations of this study. Therefore, further studies are suggested with larger cohorts to precisely compare the correlation between activity score and IL-37 taken into consideration the effects of anti-rheumatic drugs in those patients.…”
Section: Discussionmentioning
confidence: 99%